2007
DOI: 10.1176/ps.2007.58.12.1547
|View full text |Cite
|
Sign up to set email alerts
|

Does Stigma Keep Poor Young Immigrant and U.S.-Born Black and Latina Women From Seeking Mental Health Care?

Abstract: Stigma-related concerns are most common among immigrant women and may partly account for underutilization of mental health care services by disadvantaged women from ethnic minority groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
104
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 292 publications
(110 citation statements)
references
References 40 publications
4
104
1
1
Order By: Relevance
“…A closer look at our results, along with those of the other study of the SCMHC (12), reveals some consistency. Specifically, both studies found no association between SCMHC scores and current involvement in any depression treatment.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…A closer look at our results, along with those of the other study of the SCMHC (12), reveals some consistency. Specifically, both studies found no association between SCMHC scores and current involvement in any depression treatment.…”
Section: Discussionsupporting
confidence: 88%
“…The SCMHC was found in a previous study to predict desire for depression treatment but not to predict currently being in treatment (12). A closer look at our results, along with those of the other study of the SCMHC (12), reveals some consistency.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations